The Limited Pressure Model In A Thin-Walled Circular Plate, Based On A Mathematical Model With Limited Plastic Deformation. (University of Thi-Qar Journal for Engineering Sciences, 2017)
An approximated mathematical model for uniform internal pressure is studied, theoretically based on an ideal elastoplastic deformation theory and based on an equal divided thin walled circular shell,which numerically solved and used the results for testing experimentally and simulate by NX 8 Siemens finite element software under the resulted stress constrain criteria in yield stress and more 5% of it, with a limit of plastic deformation appearance in the model selected for two different material Steel 1006 and Aluminum 6053, which were under An investigation of bending test ,for estimations the resulted displacements values during elastoplasticde formation. The using of getting model given an error percentage compared with the basic theoretical mathematical equation of internal uniform pressure, which given 1.5-2%for Steel 1006 and 0.1-0.19% for Aluminum 6053, which is supported the correctness and the acceptance of using the suggested getting approximated mathematical model in this study.